Finding a New Home for Herself: A Comparison of the Joy Luck Club and Girl in Translation - Tam, Tsz Yuen (Auckland University of Technology, 2021)
This study explores two novels written by two contemporary Asian American female writers: The Joy Luck Club by Amy Tan and Girl in Translation by Jean Kwon. Both novels follow the daily experiences and family relationships of Chinese mothers who have emigrated to America and their daughters, who were born either in China or in the USA. By comparing these novels, we can see the different approaches taken by female immigrants as they create new cultural identities. The study explores the differences and similarities in the ways in which the women in these novels are shown to search for cultural identities in their new home. At the same time, it explores how the novels thus represent the images and experiences of Chinese immigrant women as being in a constant process of becoming rather than fully finished. As they struggle to find ways of being ‘at home’ in the USA, the mothers and daughters in these two novels must negotiate between past and present. They find themselves suspended between their two sides of self: Chinese and American.
Keywords: Cultural identity; Female immigrants; The Joy Luck Club; Girl in Translation